BALANCED MESSAGING FOR EXPERIENCED LAPTOP CONSUMERS - Andika Putra Pratama; Dhanu Koentoro Djati (Jurnal Sosioteknologi, 2021)
This research aims to obtain empirical evidence about the impact of “balanced messaging” (a marketing communicationpractice where both strengths and weaknesses of a product are communicated to consumers) in marketing communication on consumers’ brand loyalty. With three laptop brands being the subjects and university students in Indonesia being the sample, surveys with an experimental design were conducted. Participants (n = 90) were randomly grouped into those being exposed to product’s strengths only (Group A), product’s weaknesses (Group B), and product’s strengths and weaknesses (Group C) – with 30 participants in each group. Using ANOVA, the results indicate that balanced messaging can be as constructive as imbalanced messaging, which focuses merely on strengths in the context of brand loyalty. With several limitations, this preliminary study is expected to benefit marketers to create fairer marketing communication.